2015
DOI: 10.12998/wjcc.v3.i1.58
|View full text |Cite
|
Sign up to set email alerts
|

Vasopressors in obstetric anesthesia: A current perspective

Abstract: Vasopressors are routinely used to counteract hypotension after neuraxial anesthesia in Obstetrics. The understanding of the mechanism of hypotension and the choice of vasopressor has evolved over the years to a point where phenylephrine has become the preferred vasopressor. Due to the absence of definitive evidence showing absolute clinical benefit of one over the other, especially in emergency and high-risk Cesarean sections, our choice of phenylephrine over the other vasopressors like mephentermine, metaram… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
51
0
5

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(57 citation statements)
references
References 49 publications
1
51
0
5
Order By: Relevance
“…23,27 Even with use of these preventive measures the incidence is about 53% to 80% and without any of these preventive measures the incidence can be as high as 82%. 28,29 The primary outcome of present study was the incidence of hypotension in the two groups. The secondary outcomes studied were need for ephedrine requirement for maintaining maternal blood pressure, incidence of nausea and vomiting and neonatal outcome in terms of fetal Apgar score.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…23,27 Even with use of these preventive measures the incidence is about 53% to 80% and without any of these preventive measures the incidence can be as high as 82%. 28,29 The primary outcome of present study was the incidence of hypotension in the two groups. The secondary outcomes studied were need for ephedrine requirement for maintaining maternal blood pressure, incidence of nausea and vomiting and neonatal outcome in terms of fetal Apgar score.…”
Section: Discussionmentioning
confidence: 99%
“…Ephedrine was used for hypotension as it is readily available and is more effective for increasing arterial blood pressure with preservation of utero placental blood flow. 29 Hyperbaric bupivacaine 0.5% was used for its effective block and easy availability. 30 Crystalloid preloading may lead to dilutional anemia, decreased colloidal oncotic pressure and subsequent pulmonary edema and may not be effective even after infusing larger volumes.…”
Section: Discussionmentioning
confidence: 99%
“…[12][13][14] An observational study including a more substantial number of women demonstrated an increased risk of T2D in those with lower levels of vitamin D. 15 Diminished vitamin D levels have been linked with impaired glycemic controls. 16,17 Supplementation of vitamin D in patients with T2D has shown promising findings by lowering blood cholesterols 18 and HDL levels. 19 There is growing evidence suggesting an association of lower vitamin D levels with susceptibility to CAD and mortality.…”
Section: Introductionmentioning
confidence: 99%
“…An intravenous dose of phenylephrine has rapid onset and duration of action of 5-10 min. Tachyphylaxis accompanied with phenylephrine may be caused by the down-regulation of α adrenergic receptors and could be reversed by using hydrocortisone [4]. It was seen that cerebral oxygenation significantly decreased after phenylephrine bolus treatment but its mechanism is intriguing.…”
Section: Introductionmentioning
confidence: 99%